La contribution du Canada au développement du droit international pour la protection du milieu marin : Le cas spécial de l’Arctique - Pharand, Donat (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
Immediately after the adoption of its Arctic Pollution Prevention Act in 1970, Canada embarked on intense diplomatic efforts in a number of international for a to obtain recognition of international law principles which would serve as a basis for its legislation. These efforts were pursued mainly in three international conferences : the Stockholm Conference on the Human Environment of 1972, the London Conference of the International Maritime Consultative Organization on the prevention of pollution by ships in 1973 and the United Nations Third Law of the Sea Conference which began in 1974 at Caracas. At the 1975 session of that Conference, held in Geneva, a form of Artic clause was inserted in the first Negotiating Text and it provided that coastal States could adopt special protective measures in special areas within their exclusive economic zone, where exceptional hazards to navigation prevailed and marine pollution could cause irreversible disturbance of the ecological balance. In 1976, the provision was enlarged to enable coastal States themselves to enforce such protectives measures, instead of leaving the enforcement to the flag State, and the provision has been kept without change in all the subsequent negotiating texts of 1977, 1979 and 1980. Considering the wide consensus which this provision has received, particularly on the part of other Arctic States, it may now be regarded as part of customary international law and completely validates Canada's arctic legislation.